2021
DOI: 10.3390/jimaging7090183
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Hidden Features in Multilayered Artworks by Means of an Epi-Illumination Photoacoustic Imaging System

Abstract: Photoacoustic imaging is a novel, rapidly expanding technique, which has recently found several applications in artwork diagnostics, including the uncovering of hidden layers in paintings and multilayered documents, as well as the thickness measurement of optically turbid paint layers with high accuracy. However, thus far, all the presented photoacoustic-based imaging technologies dedicated to such measurements have been strictly limited to thin objects due to the detection of signals in transmission geometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…As a consequence, these imaging systems are limited to the investigation of relatively thin objects, not exceeding a couple of millimeters in thickness, hindering the application of the method over a wide range of objects with diverse structural and morphological features. To overcome these restrictions, a novel optimized epi-illumination (reflection-mode) PA imaging system has been built, to provide universal diagnostic information in objects of arbitrary thickness or shape [55]. The capabilities of the epi-illumination PA apparatus were first demonstrated to reveal hidden charcoal, graphite or sinopia sketch drawings in thick concealed (gypsum, limewash, overpainted) wall painting mock-ups [56].…”
Section: Pa Imaging Methods In Chmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, these imaging systems are limited to the investigation of relatively thin objects, not exceeding a couple of millimeters in thickness, hindering the application of the method over a wide range of objects with diverse structural and morphological features. To overcome these restrictions, a novel optimized epi-illumination (reflection-mode) PA imaging system has been built, to provide universal diagnostic information in objects of arbitrary thickness or shape [55]. The capabilities of the epi-illumination PA apparatus were first demonstrated to reveal hidden charcoal, graphite or sinopia sketch drawings in thick concealed (gypsum, limewash, overpainted) wall painting mock-ups [56].…”
Section: Pa Imaging Methods In Chmentioning
confidence: 99%
“…The promising capabilities of these imaging prototypes have been successfully utilized for the mapping of hidden sketches in painted mock-ups [59], as well as, the detection and study of restoration operations in an oil painting of historical significance [60]. In the latter case, it was observed that the area of the retouching was characterized by weak PA signals, due to the high acoustic attenuation properties of the restoration media, as well as, the back-reflections of [53][54][55] the main signals, resulting from the formation of various acoustic interfaces (Fig. 4d-e).…”
Section: Pa Imaging Methods In Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoacoustic imaging offers several applications in different scientific branches, ranging from biomedical to Cultural Heritage (CH) fields [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], due to its capability to provide in-depth optical absorption contrast with high spatial resolution. In the field of conservation and artwork diagnostics, it has recently found several applications, such as revealing hidden underdrawings in paintings [ 8 , 9 ], discovering degradation and retouching features in historical oil paintings [ 6 ], and uncovering text in multilayered documents [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to existing techniques considering light domes or free-form manual lighting, the article “LightBot: A multi-light position robotic acquisition system for adaptive capturing of Cultural Heritage surfaces” [ 2 ] uses a robot arm to set the light source at various positions with accuracy so that the system is adaptive to the size of the artefact and other constraints. However, to capture characteristics of paintings that are beyond its surface, the article “Revealing hidden features in multilayered artworks by means of an epi-illumination photoacoustic imaging system” [ 3 ] proposes a photoacoustic imaging system enabling the capture of hidden layers of paintings.…”
mentioning
confidence: 99%